Solitary form of nevus lipomatosus cutaneous superficialis: A rare entity with review of literature - Krishna Tadepally; Vijaya Gattu (Medical Journal of Dr. D.Y. Patil University, 2017)
A 45-year-old female presented with a history of pedunculated, soft, nodule on the right leg in popliteal region for 5 years. The lesion started as a small nodule and increased in size for 2 years and remained unchanged thereafter. The histological examination confirmed ectopic mature adipose tissue within dermis that supported the clinical diagnosis of nevus lipomatosus. This case report is of a solitary form of nevus lipomatosis cutaneous superficialis or pedunculated lipofibroma.